Rasch Measurement of the Brief Situational Test of Emotional Management in a Large Portuguese Sample. (February 2021) - da Motta, Carolina; Carvalho, Célia B.; Pato, Michele T.; Castilho, Paula
Emotional management (EM) is a crucial skill for achieving relevant biopsychosocial goals, and there has been an increased demand for the effective measurement of EM ability. The current study aimed to explore the psychometric properties of the Portuguese version of the brief Situational Test of Emotional Management (STEM-B) using the item response theory in a sample of 899 participants. The global fit indicated the model had a good adjustment, with most items aligning vertically across the logit scale and presenting an adequate range of item difficulty and fit. Differential item functioning analysis showed no differences in difficulty between genders, but some items differed according to the education level and age-groups. Overall, findings suggest the STEM-B is a psychometrically sound measure for specific testing of EM skills that has the potential to be used across cultures and fields.